The Relation of Theoretical and Applied Linguistics
216 p.
Keywords: The relationship of theoretical and applied linguistics has lately prompted numer ous debates. This volume originated at one of them. The essence of most of the chapters, of all of them except Fraser's and Davies's, was actually presented at the Round Table on "The Relationships of Theoretical and Applied Linguistics," organized during the 7th World Congress of Applied Linguistics, held in Brus sels, in August 1984. Individually and collectively the chapters assembled here offer support to the idea that applied linguistics should not be juxtaposed to theoretical linguistics; it is a field of research with theoretical as well as applied aspects. Written by different authors from a wide variety of different countries, the chapters may at times express views that are not totally consistent. Nevertheless, we believe that the variability of viewpoints counts among the merits (rather than the defaults) of this internationally written and edited volume. It is our hope that it will prove stimulating to linguists and practitioners in related fields and instructive to students. We wish to express our thanks to Albert Valdman for the interest he has shown in the volume and to record our appreciation to our editors, in particular Eliot Werner and Declan Scully, for their tolerance and patience.